Predictors of problem-solving skills among emergency medical services staff in Iran: A cross-sectional correlational study - Saeedyan, Masoud; Mohammadi, Mohammad Ali; Mirzaei, Alireza; Mozaffari, Naser (Frontiers in Psychology, 2022)
Background and aims Pre-hospital emergency technicians face many problems in the workplace daily, so the ability to solve or overcome them in the workplace is essential. This article aimed to assess the predictors of problem-solving skills among emergency medical services staff in Iran. Methods This study was cross-sectional correlational research. Using convenience sampling methods, 140 emergency medical services (EMS) staff were enrolled in the study. Response time was assessed using ASAYAR software, problem-Solving Skills (PSS) were measured using the Hepner Petersen Problem Solving Questionnaire (PSI), and Cognitive Emotion Regulation Strategies were assessed using the Garnfsky Cognitive Emotion Regulation Questionnaire. Descriptive statistics, t-test, one-way analysis of variance (ANOVA), Pearson's r correlation coefficient, and multiple linear regression analysis were applied using SPSS 14.0. Results The results of our study showed that the total mean score for problem-solving skills was 136.84(14.65) (range, 175-107 points). Multiple linear regression indicated that refocusing on planning, positive evaluation, stress management courses, delays and their causes, positive refocusing, catastrophizing, and acceptance were effective predictors of problem-solving skills in emergency personnel, accounting for 54% of the total variances. Conclusion This study is one of the first studies in this field. Based on our findings, individuals who consider their emotions and feelings when solving problems are better able to use the process of thinking and problem-solving skills. Therefore, by training people in the field of emotional regulation skills, the skills to solve problems technicians can be increased.